Tako-tsubo cardiomyopathy following catheter ablation of atrial fibrillation - Karaca, Oğuz; Omaygenç, Onur; Kılıçaslan, Fethi (Oxford University Press, 2014)
Tako-tsubo cardiomyopathy is characterized by reversible left ventricular dysfunction following emotional or surgical stress. Unlike the well-known complications of catheter ablation (CA) of atrial fibrillation (AF), Tako-tsubo cardiomyopathy has been rarely reported so far. We report a case of acute reversible left heart failure following successful CA of paroxysmal AF in a patient with a history of panic disorder.
WOS: 000351601600012
PubMed ID: 25355779
Keywords: Tako-Tsubo Cardiomyopathy; Following Catheter; Atrial Fibrillation